The intermediate filament protein synemin (SYNM) was found to be more widespread in CD117+ gastrointestinal stromal cell tumors (GIST) than the CD34 transmembrane phosphoglycoprotein: an immunohistochemical study. (3rd April 2019) - Criswell, Sheila; Taylor, Micaela; Kenwright, Kathleen; Skalli, Omar
ABSTRACT: Interstitial cells of Cajal (ICC) are the pacemaker cells in the gastrointestinal system, initiating the rhythmic systematic contraction of smooth muscle to regulate peristalsis. Benign ICC are identified immunohistochemically by positive staining for CD117, c-kit tyrosine kinase receptor. CD117 expression is maintained during the malignant transformation of ICC into gastrointestinal stromal cell tumors (GIST). However, to date, no single reliable marker for GIST has been identified by immunohistochemical (IHC) staining, and correct diagnosis depends on IHC staining results using multiple markers. This study compared the reactivities of synemin (SYNM) intermediate filament protein and CD34, a known marker for stem cells, endothelial cells, and many GIST tumors, in 54 formalin-fixed, paraffin-embedded GIST, which were determined by this study to be CD117 positive. Double-immunofluorescence (IF) staining was also used to assess whether CD117 and SYNM were co-expressed by ICC. While 81.5% of the GIST were CD34 +, 92.9% of these tumors were SYNM + . ICC were CD117 + /SYNM +, whereas mast cells were CD117 + /SYNM − . Because the percentage of CD117 + /SYNM + GIST was higher than the percentage of 117 + /CD34 + GIST, this study suggested that SYNM was a better marker than CD34 for GIST diagnosis. In addition, differential expression of SYNM and CD117 helped distinguish between ICC and mast cells.